2018
DOI: 10.3892/or.2018.6340
|View full text |Cite
|
Sign up to set email alerts
|

β‑arrestin2 promotes 5‑FU‑induced apoptosis via the NF‑κB pathway in colorectal cancer

Abstract: It has been demonstrated that β‑arrestin2 is involved in the initiation and development of many types of cancers. However, its role in colorectal cancer (CRC) remains poorly understood. The present study investigated the role of β‑arrestin2 in CRC using CRC patient tissues as well as the LoVo and HCT116 CRC cell lines. Briefly, significantly higher expression of β‑arrestin2 was observed in CRC tissues compared with normal colon tissues. In addition, the downregulation of β‑arrestin2 reduced 5‑FU‑induced apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Arrb2 inhibits cell migration, invasion, and tumorigenesis via downregulation of the AKT signaling pathway in hepatocellular carcinoma [29], and its downregulation was associated with poorer prognosis in lung cancer patients [30]. Additionally, apoptosis through the NFκB pathway is promoted by Arrb2 in colorectal cancer [52]. The data in the present study strongly support that Arrb2 negatively regulates tumorigenic activities, including proliferation, migration, and angiogenesis, in GBM.…”
Section: Discussionsupporting
confidence: 78%
“…Arrb2 inhibits cell migration, invasion, and tumorigenesis via downregulation of the AKT signaling pathway in hepatocellular carcinoma [29], and its downregulation was associated with poorer prognosis in lung cancer patients [30]. Additionally, apoptosis through the NFκB pathway is promoted by Arrb2 in colorectal cancer [52]. The data in the present study strongly support that Arrb2 negatively regulates tumorigenic activities, including proliferation, migration, and angiogenesis, in GBM.…”
Section: Discussionsupporting
confidence: 78%
“…5-Fluorouracil (5-FU) represents the first-line treatment for CRC (Vodenkova et al, 2020). A recent study found that βarr2 levels were increased in CRC tissues compared with normal colon tissues (Ren et al, 2018). In vitro studies with CRC cell lines showed that knockdown of βarr2 expression resulted in a decrease in 5-FU-induced apoptosis, while overexpression of βarr2 promoted cancer cell apoptosis (Ren et al, 2018).…”
mentioning
confidence: 99%
“…We identified the following hot spots for MetS in AAs. LDB1(LIM domain binding 1) known to regulate energy homoeostasis during diet-induced obesity [59], NPTN (neuroplastin) a gene that plays a role in signalling mechanisms [60], ARRB2 (arrestin beta 2), known to promote 5-FU-induced apoptosis via the NF-κB pathway in colorectal cancer [61], ITGB7 (integrin subunit beta 7) a gene that regulates multiple myeloma cell adhesion, migration, and invasion [62] (Figure 3). In Whites, we identified CREB1(cAMP responsive element binding protein 1 known to be associated with type 2 diabetes mellitus risk [63], NEDD4 (NEDD4 E3 ubiquitin protein ligase) which has an important role in controlling cell growth and in maintaining tissue homoeostasis [64], RAB4A (RAB4A, member RAS oncogene family), known to modulate the amiloride-sensitive sodium channel (ENaC) function in colonic epithelia [65] and STX1A (syntaxin 1A) known to play an essential role in biphasic exocytosis of the incretin hormone glucagon-like peptide 1 in type 2 diabetes [66] as an interactome hotspots (Figure 4) for MetS.…”
Section: Discussionmentioning
confidence: 99%